Requirement and Difficulties to Implement the Policy Lifecycle Model for Systems Management - Prety Diawati, Anna Gustina Zainal (International Journal of Advanced Science and Technology, 2020)
For together participation of tools, management activities, processes and managed resources the policy of an enterprise can be act as glue that hold all system and network. During deployment the gap between policy enforcement, management objectives and policy definitions are inevitable. The definition of policy rarely fulfills all the requirement of management and it is difficult to understand the definition of policy. In daily management activities often system administrators circumvent policies unintentionally or intentionally or ignore them. For managing the complex system it provide a solution of problem by policy based management system. To simplify and large automation of management procedure it is very necessary.